Effects of feeding Rumensin® in a mineral mixture on steers grazing native grass pastures - Brazle, F.K.; Laudert, S.B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four hundred sixty-nine English and Continental cross yearling steers grazed on native grass pastures over a 2-year period. Rumensin® was added (1,620 g/ton) to the mineral mixture in half of the pastures. Some of the pastures were used from April 23 to July 15 and the remainder from April 23 to August 15. The pooled data for the grazing periods indicated that Rumensin supplemented steers gained 7.7% faster(P<.05) and consumed 32% less mineral (P<.05) compared to the control steers.
Keywords: Beef; Rumensin; Native grass; Mineral